PENGARUH CELEBRITY ENDORSER DAN TESTIMONIAL PRODUK TERHADAP KEPUTUSAN PEMBELIAN MASKER ORGANIK MUDDY BUDDY SECARA ONLINE - Pratiwi, Friska Dian; Andayani, Sri; Maruta, IGN Anom (Universitas 17 Agustus 1945 Surabaya, 2020)
Promotion is the most important thing for business owners. Promotional methods that are currently popular is using celebrity endorsers and product testimonials. This research entitled